PERLINDUNGAN HUKUM PETANI KERAPU TERHADAP PENCEMARAN LINGKUNGAN OLEH PT PELABUHAN INDONESIA II (PERSERO) CABANG PANJANG - Tara Fitria Rozika (Jurnal Hukum Lex Generalis, 2024)
The impacts that occur due to waste disposal by PT Pelabuhan Indonesia II (Persero) Cabang Panjang which indirectly results in damage to the ecosystem in the sea around Ringgung Island, Pasaran, and Pahawang. So that the community who work as grouper farmers are harmed due to the damage to the ecosystem so that the fish they farm die en masse. So that the grouper farmers sue for the losses they have received. The results obtained are known that the permit for dredging the sail current has been obtained but related to dumping has not been obtained which results in exceeding the sea water quality standards. As well as legal protection for the community, there are 3 existing legal instruments, namely administrative law, criminal law, and civil law. The grouper farmer community has also tried to obtain legal protection through these 3 instruments.